Brief introduction to distributions and to Hörmander spaces Bp,k - Alejandro Ortiz Fernández (Selecciones Matemáticas)
Partial differential equations (PDE’s) are, we believe, little known in our country, especially at a medium-advanced level, in particular, their historical roots and methods developed in their evolution. The objective of this article is to contribute to a knowledge in this direction especially to colleagues and students who are interested in studying and researching in this central Branch of mathematics. As a model we have chosen H¨ormander’s book, [1], whose study and teaching will be a sign of great progress in this direction in our country. In this article we only give an introduction to part I dedicated to functional analysis and which includes chapters I and II that deal with the theory of distributions and some special spaces of distributions, respectively.